2009
DOI: 10.1007/s10772-009-9059-z
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and implications of veins theory: a discussion of discourse cohesion

Abstract: The paper deals with the cohesion part of a model of global discourse interpretation, usually known as Veins Theory (VT). By taking the notion of nuclearity (though ignoring relations), from the Rhetorical Structure Theory, VT computes strings of discourse units, called veins, from which domains of accessibility can be determined for each discourse unit. VT's constructs best fit with an incremental view on discourse processing. Linguistic observations that lead to the elaboration of the theory are presented. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They concluded that multilingual WSDs are more precise than monolingual ones. Cristea (2009) examined cohesion as part of the veins theory. He computed strings of discourse units to find the best fit, taking an incremental view of discourse processing, linguistic observations, cognitive shortterm memory, and online summarization.…”
Section: Examples Of How To Pick a Good American President From 2016 ...mentioning
confidence: 99%
“…They concluded that multilingual WSDs are more precise than monolingual ones. Cristea (2009) examined cohesion as part of the veins theory. He computed strings of discourse units to find the best fit, taking an incremental view of discourse processing, linguistic observations, cognitive shortterm memory, and online summarization.…”
Section: Examples Of How To Pick a Good American President From 2016 ...mentioning
confidence: 99%